Peran Fungsi Eksekutif Siswa SMP dalam Menyelesaikan Soal Cerita Ditinjau dari Kemampuan Matematika - Cicik Fauziyah (MATHEdunesa, 2020)
Mathematics is a subject that has an important influence in every daily life. So that mathematics becomes the subject of learning at almost every level of education. However, many people complain that they have difficulty working on math problems. One of the factors that influence someone in solving math problems is the executive function. This study will conduct research to describe the role of the executive function of students in learning mathematics. The method used in this is descriptive qualitative research. Researchers will explore the role of junior high school students' executive function in solving story problems with the subject of three eighth grade students from 5 Junior High School of Surabaya. Data collection techniques used were tests and interviews. The results showed that the level of mathematical ability played a role in students' ability to solve story problems. There is an indication that the higher the level of mathematical ability, the higher the executive function they have and the students will solve the form of the story problem better. The conclusion in this study is that there is an important role of the executive function on students' ability to solve story problems in mathematics.